Specific food intolerance: its place as a cause of gastrointestinal symptoms. Issue 2 (February 1985) - Farah, D A; Calder, I; Benson, L; MacKenzie, J F
Abstract : Thirteen out of 49 patients suspected of having specific food intolerance after withdrawal and reintroduction of specific foods, were further subjected to double blind placebo controlled food challenges. Only three of these subjects were thus shown to have proven specific food intolerance. Of the remaining 10, nine were strong 'placebo reactors'. The study suggests that a small number of patients with gastrointestinal symptoms have verifiable specific food intolerance but that a greater number have symptoms attributable to psychogenic causes.